A new chapter in Indo-U.S. relations? - Ganguly, Sumit (2016)
DOES President Bush’s recent visit to India presage a new era in relations between India and the United States? The answer is unequivocally positive even though some potential pitfalls still lurk both in India and the US. The evolution of the relationship, in considerable measure, will depend on how both sides handle extant and future differences.